Pengaruh Literasi Keuangan dan Sikap Peduli Lingkungan Terhadap Keputusan Investasi Hijau Generasi Z - Ketut Tanti Kustina; I Made Agus Adi Kurniawan; I Gst Ayu Diah Utari (Universitas Warmadewa, 2024)
Green investment refers to allocating funds to projects or financial assets that support sustainability principles and positively impact the environment or society. This study aims to investigate how Generation Z's financial literacy and environmental concerns influence green investment decisions according to the Theory of Reasoned Action. Google Form is a data collection tool distributed to Generation Z in Denpasar, and 100 respondents accepted it. The researcher employs multiple linear regression analysis. The research findings indicate that financial literacy has a positive influence on green investment decisions, and environmental concern has a significant positive impact on green investment decisions.